Development of a Digital Product Passport for iPads to Enhance Student Sustainability Practices - Ko, Junwon; Okafor, Nnaemeka; Badurdeen, Fazleena; Wang, Peng (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper proposes a generic framework for the design and development of Digital Product Passports (DPPs) applicable across various products, sectors, and developers. The framework, established considering information requirements and existing approaches identified in DPP literature, comprises four key phases: (1) Defining the Foundations; (2) Design and Development; (3) Testing and Refinement; (4) Deployment and Evaluation. Its application is demonstrated through the development of a Digital iPad Product Passport for the University of Kentucky iPad initiative (UK-DiPP). An app-based UK-DiPP prototype is presented with three core intended functionalities: (1) Charging Pattern, (2) Battery Usage, and (3) iPad Lifecycle, aiming to promote sustainable charging practices, extend battery lifetime, support end-of-life (EoL) management, enhance sustainability awareness on campus, and mitigate the negative environmental impacts associated with iPad use and disposal. Challenges as a third-party DPP developer, including limited data accessibility and technical obstacles, are discussed with potential workarounds and solutions. This research contributes to the practical development and implementation of DPPs by offering a versatile framework and showcasing real-world application.